Phylogenetic and phenotypic characterisation of Sirococcus castaneae comb. nov. (synonym Diplodina castaneae), a fungal endophyte of European chestnut. Issue 8 (August 2017) - Meyer, Joana B.; Trapiello, Estefanía; Senn-Irlet, Beatrice; Sieber, Thomas N.; Cornejo, Carolina; Aghayeva, Dilzara; González, Ana J.; Prospero, Simone
Abstract: In this paper we resolve the taxonomic status of the fungus Diplodina castaneae (Ascomycetes, Diaporthales, Gnomoniaceae) which occurs on the European chestnut ( Castanea sativa ) as endophyte and as the causal agent of Javart disease. Specimens from Switzerland, Spain, and Azerbaijan were sequenced at five nuclear loci (β-tubulin, EF-1α, ITS, LSU, and RPB2). Phylogenies were inferred to place D. castaneae in the Gnomoniaceae family. Moreover, growth rates and morphological characteristics on different agar media were assessed and compared to those of Gnomoniopsis castaneae, which can easily be confused with D. castaneae . Based on morphological and phylogenetic characteristics, we propose to reallocate D. castaneae to the genus Sirococcus, as S. castaneae comb. nov.